2019
DOI: 10.1002/brb3.1334
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal transcriptome reveals novel targets of FASD pathogenesis

Abstract: Introduction Prenatal alcohol exposure can contribute to fetal alcohol spectrum disorders (FASD), characterized by a myriad of developmental impairments affecting behavior and cognition. Studies show that many of these functional impairments are associated with the hippocampus, a structure exhibiting exquisite vulnerability to developmental alcohol exposure and critically implicated in learning and memory; however, mechanisms underlying alcohol‐induced hippocampal deficits remain poorly understood. By utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 85 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…Development of the nervous system is a highly regulated and organized molecular process controlled by gene expression in response to environmental cues. This well controlled system is extremely vulnerable to alcohol during development which has been shown to alter expression of genes involved in a range of critical processes [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Developmental alcohol exposure has been shown to have both short-term [ 28 , 30 ]; and long-term consequences to the transcriptome [ 25 , 27 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Development of the nervous system is a highly regulated and organized molecular process controlled by gene expression in response to environmental cues. This well controlled system is extremely vulnerable to alcohol during development which has been shown to alter expression of genes involved in a range of critical processes [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Developmental alcohol exposure has been shown to have both short-term [ 28 , 30 ]; and long-term consequences to the transcriptome [ 25 , 27 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that chronic alcohol administration led to changes in genes associated with cell cycle arrest and negative regulation of cell proliferation in the hippocampus of adolescent rats. On the other hand, in the study by Lunde‐Young et al that investigated gene expression profiling in the hippocampus of foetus of timed‐pregnant rats exposed to chronic binge alcohol, genes related to xenobiotic metabolism signalling and alanine biosynthesis were changed in male offspring, while genes involved in proline and citrulline biosynthesis were changed in females . Their results demonstrated indirect chronic exposure to alcohol during pregnancy affects mainly amino acid synthesis in the developing hippocampus.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, the effects of alcohol on the hippocampus at the cellular and molecular levels have been studied through large‐scale transcriptome profiling. The Lunde‐Young group found vulnerable genes to alcohol in the hippocampus of prenatal offspring of timed‐pregnant Sprague‐Dawley rats and their genetic networks after indirect exposure to alcohol on gestational day using RNA‐sequencing (RNA‐Seq) technology . Their results help understand neuropathogenesis of foetal alcohol spectrum diseases (FASD).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in adult females LTP is intact (80) and even enhanced in early adults exposed to EtOH during late developmental stages (78). The sex-specific effects on synaptic plasticity are corroborated by sexually dimorphic transcriptional FAE-induced modifications in hippocampal gene expression (82).…”
Section: Synaptic and Circuit Defects Underlying Fae-induced Learningmentioning
confidence: 96%